Positive psychology pioneers: Ed Diener's power and potential to influence mental health nursing. (2nd August 2022) - Macfarlane, Jan
Abstract : This article is the third in a series that celebrates the work of positive psychologists and how their work has the power and potential to influence mental health nursing practice. Focusing on the contribution of Professor Ed Diener (1946–2021), and his work on subjective wellbeing, will help bring interest and understanding to this exciting and developing area of mental health nursing practice.